Principles and practices of a design-led approach to innovation. Issue 3 (2nd October 2017) - Wrigley, Cara
Abstract: Innovation activities worldwide have been enhanced by the use of design, due to organizations utilizing it to create more effective methods of problem solving. Though there is evidence to suggest the concept of design-led innovation (DLI) is gathering momentum – both within design practice and academia, little has been published to assist in undertaking such an activity. Recent studies have categorized DLI as a perspective rather than an evidence-based practice. This paper reflects on both extant literature and seven longitudinal DLI case studies to produce 20 best practice principles aimed to serve as a set of 'ground rules' for DLI practitioners. Its purpose is to foster a common understanding of DLI as a research domain and process. Arrived at in consultation with DLI Catalysts embedded within various organisations over a 12–24 month project implementation timeframe, these 20 principles represent a set of capabilities analyzed as being not only essential for the implementation of DLI, but of great assistance in overcoming its associated challenges. The author presents future work in this newly established area, as well as highlighting the principles themselves as a focus of future research. This is the first paper which distils the principles of DLI from a non-literature perspective.